Proton NMR spectral study of UV treated live Escherichia coli Bacteria / by Michael Sorokopud. - Sorokopud, Michael (My University, 2010)
The lethal effects of ultraviolet radiation on microorganisms have been known and utilized for many years. In sufficiently high photon fluences, light and in particular, UV light, is an effective and subtle means of killing or at least immobilizing most, if not all cells and micro-organisms. Because of their small size, light can penetrate the enclosing protective walls and enter the inner volumes where it can break organic bonds in components that are vital to cell function. Despite the fact that a very low dose of UV light (1-9 mJ/cm2) has been shown to inactivate many micro-organisms, there remains a dearth of biological information about light induced effects in molecules and their interactions within living microbial systems. The use of 1H NMR as a spectroscopic tool was chosen to undertake an examination of the possible effects resulting from exposing 'E. coli' to lethal fluencies of UV radiation. Once sample preparation, treatment, and NMR mounting methods were optimized, the high sensitivity and high resolution capabilities of the method produced reproducible results for a series of experiments. These results reveal significant changes in the ratio of the 1H NMR spectra of the treated to untreated ' E.coli' samples when the treated sample was exposed to a lethal fluence of 275nm light. Photons at the 275nm wavelength, used in this study, have enough energy to break all of the principle bonds in an organic molecule. The difference spectrum between treated to untreated samples appears to be fitted well using specific component spectra from these groups of compounds. Increases in NMR peak amplitudes are observed and appear to be correlated with the spectral locations of several amino acids, membrane components and several sugars/saccharides. Increases in peak intensities of 4-8% were observed in the 0.8-1.1 ppm chemical shift region, characteristic of lipid and amino acid groups. A 3.5-4% increase was observed in the 2 ppm and 3.4-4 ppm region characteristic of various sugars and possibly amino acid components.
Keywords: Escherichia coli - Effect of ultraviolet radiation on; Escherichia coli - Spectra